Implementasi Teknologi Digital dalam Proses Pembelajaran di Sekolah Dasar - Trismiani (Yayasan Darussalam Bengkulu, 2024)
This study aims to explore the implementation of digital technology in the learning process in Elementary Schools. Digital technology has become an integral part of modern education, offering a variety of tools and resources that can enhance students' learning experiences. The research method used is a qualitative approach with a case study design. Data were collected through in-depth interviews with teachers, classroom observations, and analysis of curriculum documents related to the use of digital technology. The results of the study indicate that the use of digital technology, such as interactive learning software, educational applications, and social media, can increase student motivation and engagement in the learning process. In addition, the study also found challenges faced by teachers, such as lack of adequate training and limited access to technology. To overcome these challenges, it is recommended that schools provide adequate training for teachers and improve technology infrastructure. In conclusion, the implementation of digital technology in Elementary Schools can enrich the learning process, as long as it is supported by appropriate policies and adequate resources.